An exploration of two-dimensional materials for solar energy harvesting - COLIBABA, STEFANA ANAIS (Trinity College Dublin. School of Physics. Discipline of Physics, 2020)
The rise in energy demand around the globe can only be met with sustainable and long-term reliance on alternative renewable energy sources. In this context, the goal of this thesis is to conceive a method through which two-dimensional materials and heterostructures thereof can be ranked in terms of their photoabsorption. Firstly we have explored the theoretical limitations of realistic predictions for the photoconversion efficiency obtained with ab-initio methods such as density functional theory. We have studied silicon and methyl ammonium lead iodide and have found that the efficiency is largely affected by the inherent level of disorder in the system. This rendered the efficiency study intractable from an ab-initio perspective. However, the short circuit current density, $J_{sc}$, has been proven to be reliably determined within our model even in the absence of an empirical treatment. We have designated the short circuit current density at 95\% of its maximum saturation value as our ab-initio photovoltaic descriptor, together with the corresponding active layer thickness. This effectively allowed us to rank materials according to their absorption ability.\\ Next we have looked at the HfS$_{2}$/PtS$_{2}$ heterostructure, a system with a type II band alignment, in order to identify unique peaks that could be associated with interlayer transitions. We have decomposed the dielectric function into its constituting intra-layer, inter-layer and mixed components. We have found that the inter-layer absorption was much smaller in amplitude than the other components. However, compressing the two layers resulted in the creation of a valence impurity band, which led to the formation of a well-isolated peak at the absorption edge. This new feature of the absorption spectrum was associated with inter-layer transitions.\\ In the last part of our work, we have studied the process of "band nesting" in transitional metal dichalcogenides and transitional metal halides. We have performed several classifications of the compounds based on the gradient of the energy difference between the top valence and bottom conduction band mapped onto the irreducible Brillouin zone. We have found similar human discernible patterns in the resulting groups, which justified the emerging groups. Moreover, we investigated the joint density of states in two-dimensional transitional metal dichalcogenides and halides. We have noticed the roughly linear relation between the joint density of states and the imaginary part of the dielectric function spectra, especially for the in-plane component of the imaginary part of the dielectric function. Based on this approximation, we have calculated the absorption coefficient and its integrated value over the energy range of the solar spectrum. We have ranked all materials according to the unapproximated and approximated absorption coefficient integral values and found that the two rankings matched extremely well. We have concluded that the joint density of states is a good descriptor for photovoltaic absorption in transitional metal dichalcogenides and transitional metal halides.
APPROVED
Keywords: photovoltaics, absorption, density functional theory, van der Waals heterobilayers, joint density of states, two-dimensional material ranking